2010
DOI: 10.1016/j.ijhcs.2010.03.004
|View full text |Cite
|
Sign up to set email alerts
|

‘To play or not to play’: A cross-temporal investigation using hedonic and instrumental perspectives to explain user intentions to explore a technology

Abstract: The present research extends prior work on the relationship between users and technology by examining users' intention to explore a technology. Drawing on exploration and individual motivation theories, we developed and tested a model examining the effects of hedonic (i.e., personal innovativeness and cognitive absorption) and instrumental (i.e., performance expectancy and image enhancement) factors on individuals' intentions to explore a technology over time. Based on a study of 94 users exposed to a new tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(85 citation statements)
references
References 98 publications
(147 reference statements)
5
77
0
3
Order By: Relevance
“…After they start deriving utilitarian gratifications, hedonic gratifications get less important and predictive in SNS usage. Magni et al's [16] work showed that, as time passes, the effects of hedonic factors decrease whereas the effects of utilitarian factors (e.g., performance expectancy) increase people's intentions to explore technologies. When people initially use SNS, they may only use some basic functions that are primarily designed to serve hedonic gratifications.…”
Section: Data Analyses and Resultsmentioning
confidence: 99%
“…After they start deriving utilitarian gratifications, hedonic gratifications get less important and predictive in SNS usage. Magni et al's [16] work showed that, as time passes, the effects of hedonic factors decrease whereas the effects of utilitarian factors (e.g., performance expectancy) increase people's intentions to explore technologies. When people initially use SNS, they may only use some basic functions that are primarily designed to serve hedonic gratifications.…”
Section: Data Analyses and Resultsmentioning
confidence: 99%
“…HM affects behavioral intentions (Liao and Lin, 2007;Taylor and Venkatesh, 2010). However, it differs across stages of technology adoption.…”
Section: Hedonic Motivations (Hm)mentioning
confidence: 99%
“…It is generally found to be an important factor to influence intention to adopt mobile internet (Venkatesh et al, 2012), even though Magni, Taylor and Venkatesh (2010) argue that its influences could be varied across different stages of technology adoption. Despite the different findings, hedonic motivation is important as consumers tend to use a mobile entertainment which bring them joy and happiness (Leong, Ooi, Chong & Lim, 2013a), or when it is considered as fun, entertaining and provides pleasure.…”
Section: Hedonic Motivationmentioning
confidence: 99%